Website as Co-Created Decision Support System Towards Enhanced Experience of Solo City Tourism - Putro, Utomo Sarjono; Mayangsari, Lidia; Siallagan, Manahan; Novani, Santi (School of Business and Management Institut Teknologi Bandung, 2016)
Abstract. The linkage among information-intensive era, technology, and tourism industry build inseparable genetic relationship which is supposed to be realized in practice. Let alone in this digital era, the urgency to exploit information to the next level resulted in the need to bring a higher game on the technology in order to manage information effectively and efficiently. Tourism industry is categorized as complex system regarding the components substituted it. The diverse elements which interact with dynamics pace give birth to complex tasks to manage by the responsible parties and consequently enhance experience in tourism industry. Competing with complex situation, computerized decision system is urgently needed to collect and also distribute accurate knowledge of tourism industry, collaborate with both supporting public and private sectors, and gain rationality for all stakeholders in the system. Solo city, known also as Surakarta and located in Central Java (Indonesia), is obliged to do its tourism industry justice as it is an important vehicle for regional development of the city. Tourism industry of Solo city represents the major and significant contributor to the local economy to the point where tourism is the brand of Solo city. Taking the prior research finding, value orchestration platform to promote tourism in batik Solo industrial cluster into the reference, this study improves the model by highlighting the duality function the tourism website supposed to have using hashtag (#) minings principle as the latest user interface technology. This study proposes a collaborative website platform as a co-created decision support system to enhance tourism experience for tourist as consumer and optimize management process for Department of Culture and Tourism of Solo city as provider.Keywords: Decision support system, hashtag mining, service-dominant logic, solo city, tourism experience